Changes in the aggregate labor force participation rate - Julie L. Hotchkiss (Economic Review, 2009)
Human capital is a vital component in the production process, so the size of the labor force can profoundly affect the potential for economic growth. In the United States, the overall labor force participation rate (LFPR)the percent of the population supplying labor to the marketbegan to grow in the mid-1960s, mainly because of the rise in women's LFPR. But since 1997 the aggregate LFPR has been generally declining. Many researchers have linked this decline to demographic factors, chiefly the drop in labor force participation among young people and working-age women. This article presents a simple methodology for decomposing changes in the aggregate LFPR over time into demographic group changes in both labor force participation behavior and population shares. The decomposition reveals that a decline in the population shares of working-age men and women was actually the driving force behind the recent drop in the aggregate LFPR, outweighing the effect of the declining participation rates of women and youth. This simple method demonstrates how little information is needed to evaluate the historical evolution of the aggregate LFPR and to make projections of its future path that are a close match to estimates from more complex structural forecasting models.
Keywords: J11; J21; E24; 330; labor force participation; decomposition; forecasting